Construct validity evidence for a measure of peer athletic reputation (PAthR) in high school physical education - Howle, T.; Whipp, P.; Gairns, F.; Thornton, A.; Rebar, Amanda; Jackson, B. (Elsevier BV, 2016)
© 2016 Elsevier Ltd. Grounded in the work that has been conducted on peer academic reputation in educational settings, our aim was to develop and provide initial construct validity evidence for a modified instrument designed to assess peer athletic reputation (PAthR). In phase 1, we devised a series of items to assess PAthR. In phase 2 (n = 399), and approximately one month later in phase 3 (n = 374), female high school physical education (PE) students completed a series of questionnaires that included the PAthR instrument. Analyses indicated that PAthR was (a) represented as a unitary construct, (b) positively associated across time points, (c) positively associated with indicators of desirable peer interactions (e.g., peer relatedness support, peer relatedness need satisfaction) and PE experiences (e.g., intrinsic motivation, perceived competence), and (d) negatively associated with indices considered to be less adaptive in nature (i.e., anxiety, amotivation). These findings provide preliminary support for a novel approach to the measurement of peer reputation in PE, and demonstrate evidence of the nomological net with which this concept may be associated.